1996
DOI: 10.1159/000154829
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroid State on Characteristics Determining the Susceptibility to Oxidative Stress of Mitochondrial Fractions from Rat Liver

Abstract: We have studied biochemical and functional characteristics of three mitochondrial fractions resolved by differential centrifugation from the liver of rats in different thyroid states. In particular, the relation between cytochrome and antioxidant content of the mitochondria and their oxygen consumption and response to oxidative stress has been investigated. The cytochrome content is greater in the fractions at higher density, whereas the opposite pattern is shown for antioxidant level. These biochemical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…This view has been supported by recent studies showing that the mitochondrial population of the liver could be resolved by differential centrifugation (at 1,000, 3,000 and 10,000 g, respectively) in fractions representing different forms in the mitochondrial growing-maturation-degradation cycle [112]. Such fractions are characterized by different oxidative and antioxidant capacities and effectiveness to oppose oxidative stress [112]. In particular, the light fractions (M 3 and M 10 fractions), with high oxidative capacity and low susceptibility to oxidative stress, represent transitional forms in the process of development into the heavy mitochondrial structures (M 1 fraction) exhibiting low oxidative capacity and high susceptibility to oxidative stress.…”
Section: Effects Of Exercise On Mitochondrial Subpopulationsmentioning
confidence: 70%
See 3 more Smart Citations
“…This view has been supported by recent studies showing that the mitochondrial population of the liver could be resolved by differential centrifugation (at 1,000, 3,000 and 10,000 g, respectively) in fractions representing different forms in the mitochondrial growing-maturation-degradation cycle [112]. Such fractions are characterized by different oxidative and antioxidant capacities and effectiveness to oppose oxidative stress [112]. In particular, the light fractions (M 3 and M 10 fractions), with high oxidative capacity and low susceptibility to oxidative stress, represent transitional forms in the process of development into the heavy mitochondrial structures (M 1 fraction) exhibiting low oxidative capacity and high susceptibility to oxidative stress.…”
Section: Effects Of Exercise On Mitochondrial Subpopulationsmentioning
confidence: 70%
“…The focal nature of the mitochondrial derangement was explained by McCutcheon et al [98] admitting that the mitochondrial population of muscle consists of mitochondria of different ages and thus of varying susceptibility to exercise-induced alterations. This view has been supported by recent studies showing that the mitochondrial population of the liver could be resolved by differential centrifugation (at 1,000, 3,000 and 10,000 g, respectively) in fractions representing different forms in the mitochondrial growing-maturation-degradation cycle [112]. Such fractions are characterized by different oxidative and antioxidant capacities and effectiveness to oppose oxidative stress [112].…”
Section: Effects Of Exercise On Mitochondrial Subpopulationsmentioning
confidence: 85%
See 2 more Smart Citations
“…It has been demonstrated that hyperthyroidism leads to accelerated free radical formation [183]. Conversely, increased free radical formation enhances intracellular scavenging enzymes, like SOD, in experimentally induced hyperthyroidism [141].…”
Section: Antioxidant Statusmentioning
confidence: 99%